LC-MS/MS Metabolite Profiling of Meistera aculeata (Roxb.) Škorničk. & M.F. Newman (Susube) and Preliminary Brine Shrimp Lethality Screening - Megawati Megawati; Muhamad Jalil Baari; Carla Wulandari Sabandar (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
Meistera aculeata (Roxb.) Škorničk. & M.F. Newman is a species of the Zingiberaceae family distributed in Southeast Sulawesi, Indonesia, particularly in Konawe Regency. The fruits are traditionally consumed and used as a culinary spice by the Tolakinese community. However, information regarding its metabolite composition and biological activities remains limited. This study aimed to profile putative metabolites using LC–MS/MS and to evaluate preliminary lethality using the Brine Shrimp Lethality Test (BSLT). Dried powders of rhizomes, stems, leaves, and fruits were extracted by maceration with methanol. Metabolite annotation was performed using LC–MS/MS, while cytotoxic potential was assessed through BSLT. The analysis tentatively detected 13 metabolites dominated by flavonoids, phenylpropanoids, and terpenoids. Methanol extracts of rhizomes, stems, leaves, and fruits showed toxic activity with LC₅₀ values of 56.6 ± 9.9, 70.1 ± 8.1, 71.6 ± 9.3, and 115.5 ± 13.5 μg/mL, respectively, compared with K₂Cr₂O₇ as a positive control (LC₅₀ 11.5 ± 1.6 μg/mL). Literature comparison suggests that although these metabolites have been reported in other plant species, their occurrence in M. aculeata is reported here for the first time. The BSLT results indicate preliminary cytotoxic activity, suggesting the presence of bioactive compounds. These findings support further chemotaxonomic and pharmacological investigations to identify potential marker compounds and expand knowledge of metabolites within the Zingiberaceae family, particularly the genus Meistera.